Pengaruh Kepemimpinan Kepala Sekolah, Budaya, dan Peran Komite Sekolah terhadap Kepuasan Pelayanan - Teddy Manueke; Deitje A. Katuuk; Viktory N. J Rotty; Jeffry S. J. Lengkong (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2021)
This study aims to measure two types of variables, independent variable consisting of the principal's leadership, school culture and school committees and the dependent variable, service satisfaction. The subjects of this study were teachers of SMK Negeri in Bitung totaling 241 with a sample of 71 people. The method used is a descriptive analytical survey method and uses correlational analysis. The analysis technique used is Pearson Product Moment Correlational Analysis. The results showed that there was a significant influence of principal's leadership on service satisfaction of State Vocational Schools in Bitung City by 44.9%. There is an influence of school culture on service satisfaction of State Vocational Schools in Bitung City by 49%. There is an influence of school committees on service satisfaction of State Vocational Schools in Bitung City by 33.7%. There is an effect of principal leadership and school culture together on service satisfaction of State Vocational Schools in Bitung City by 46.3%. There is an influence of the leadership of the principal and the school committee together on the service satisfaction of State Vocational Schools in Bitung City by 46.5%. There is an influence of school culture and school committee together on service satisfaction of State Vocational Schools in Bitung City 45.4%. There is a joint influence of the principal's leadership, school culture and school committee on service satisfaction of State Vocational Schools in Bitung City by 47.9%. Keywords: principal’s leadership, school culture, school committee, service satisfaction Penelitian ini bertujuan mengukur dua jenis variabel, yaitu: variabel bebas yang terdiri atas kepemimpinan kepala sekolah, budaya sekolah dan komite sekolah serta variabel terikat yaitu variabel kepuasan pelayanan. Subjek penelitian ini adalah guru-guru SMK Negeri di Bitung yang berjumlah 241 dengan penarikan sampel sebanyak 71 orang. Metode yang digunakan adalah metode survey yang bersifat deskriptif analitis dan menggunakan analisis korelasional. Teknik analisa yang digunakan adalah Analisis Korelasional Pearson Product Moment. Hasil penelitian menunjukkan terdapat pengaruh yang signifikan kepemimpinan kepala sekolah terhadap kepuasan pelayanan SMK Negeri di Kota Bitung sebesar 44,9%. Terdapat pengaruh budaya sekolah terhadap kepuasan pelayanan SMK Negeri di Kota Bitung sebesar 49%. Terdapat pengaruh komite sekolah terhadap kepuasan pelayanan SMK Negeri di Kota Bitung sebesar 33,7%. Terdapat pengaruh kepemimpinan kepala sekolah dan budaya sekolah secara bersama-sama terhadap kepuasan pelayanan SMK Negeri di Kota Bitung sebesar 46,3%. Terdapat pengaruh kepemimpinan kepala sekolah dan komite sekolah secara bersama-sama terhadap kepuasan pelayanan SMK Negeri di Kota Bitung sebesar 46,5%. Terdapat pengaruh budaya sekolah dan komite sekolah secara bersama-sama terhadap kepuasan pelayanan SMK Negeri di Kota Bitung 45,4%. Terdapat pengaruh kepemimpinan kepala sekolah, budaya sekolah dan komite sekolah secara bersama-sama terhadap kepuasan pelayanan SMK Negeri di Kota Bitung sebesar 47,9%. Kata Kunci: Kepala Sekolah, Kepemimpinan, Budaya, Komite, Kepuasan Pelayanan